Robotic guided waterjet cutting technique for high tibial dome osteotomy: A pilot study. Issue 3 (12th May 2017) - Suero, Eduardo M.; Westphal, Ralph; Zaremba, David; Citak, Musa; Hawi, Nael; Citak, Mustafa; Stuebig, Timo; Krettek, Christian; Liodakis, Emmanouil
Abstract: Background: Oscillating saws generate high levels of heat (up to 150°C), which can lead to tissue necrosis, delayed healing and infection. Abrasive waterjet‐cutting techniques have been described as a new tool to perform bone cuts, with less heat generation. Methods: Four lower‐limbs of four human alcohol conserved cadavers were tested. Navigation references were attached to the tibia and an intraoperative fluoroscopy‐based 3D scan was obtained. A 1.2 mm diameter nozzle was attached to a robotic arm, which was guided to follow a pre‐specified path. In addition, a self‐designed jet‐absorber was applied to protect the posterior neurovascular structures. Magnesium was added as an abrasive substance to improve the cutting ability of the waterjet. Results: In all four cadavers, the osteotomies could be carried out as planned, resulting in smooth cut surfaces. No damage to the soft‐tissues was observed. Conclusions: The advantages of abrasive waterjet‐cutting give it great potential in orthopaedic surgery. A current disadvantage is the amount of magnesium solute that is left on the surgical field and can be harmful to the patient.